Fosfato monoamônio revestido com polímeros no plantio das culturas de milho irrigado e cana-de-açúcar - Souza, Carlos Henrique Eiterer de (2012)
Phosphorus (P) is the most limiting nutrient, in tropical conditions, for crop yield, mostly due to its low contents and high fixation in soils. Moreover, it is common to observe low efficacy of phosphate fertilizers, with plant absorption varying from 20% to 30%. Therefore, the reduction of phosphate fertilizers expenses and, or, increasing its efficacy, coverage of fertilizers with polymers that allow a slow and gradual release of the nutrient has been used as an alternative. Thus, this study evaluated the development of maize and sugar-cane as a function of P application as polymer covered monoammonium phosphate, in different locations and cropping systems, in relation to quantitative and qualitative nutritional parameters of yield. The experiment with maize was done in a no tillage irrigated area, while experiments with sugar-cane were done in first year commercial areas of two mills, Guaíra, in Guaíra (SP) and WD, in Varjão de Minas (MG). All experiment designs were randomized blocks as a 4x2 + 1 factorial (control with no P fertilization). Treatments consisted of four P doses (50, 100, 150 and 200 kg ha-1 P2O5) applied as monoammonium phosphate with or without polymer covering. The information generated indicated that the technology is promising and that there is a lack of basic knowledge about the behavior of polymers in different production environments. In can be concluded in the maize experiment that the polymer covered source had greater agricultural efficacy, allowing an increase in crop yield. No significant differences between the sources were found in the sugar-cane experiment at Guaíra (SP). In contrast, at the mill WD, the covered source resulted in increases in stalk and total sugar yield by unit area. In this experiment, the models generated presented direct correlation between stalk yield, sugar yield and P leaf contents.